MXene-based fiber, electromagnetic shielding fabric as well as preparation method and application of MXene-based fiber and electromagnetic shielding fabric
By combining MXene with materials such as polyvinyl alcohol and polymethylene polyphenylene polyisocyanate, MXene-based fibers were prepared by wet spinning technology, and through chemical crosslinking treatment, the poor spinability and stability of MXene materials in electromagnetic interference shielding and functional textiles were solved, and high-performance electromagnetic shielding fabrics were achieved.
Patent Information
- Application Number
- CN202510017648.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-06
AI Technical Summary
Existing MXene materials have problems such as poor spinning, weak interface interactions, poor tensile strength and ductility in electromagnetic interference (EMI) shielding and functional textiles, and are also unstable in extreme environments.
MXene-based fibers were prepared by combining MXene with materials such as polyvinyl alcohol (PVA) and polymethylene polyphenylene polyisocyanate (PMDI), and the mechanical properties and electromagnetic shielding properties of the fibers were improved by chemical crosslinking treatment.
It realizes the good flexibility, mechanical properties and multimodal response of MXene-based fibers, can maintain stability in extreme environments, dynamically adjust shielding performance, and is suitable for wearable electromagnetic interference shielding fabrics and other fields.
Smart Images

Figure CN119824564A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electromagnetic interference shielding materials, and specifically relates to a MXene-based fiber, an electromagnetic shielding fabric, and a preparation method and application thereof, and specifically to applications in the direction of electromagnetic shielding. Background Art
[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.
[0003] Electromagnetic interference (EMI) or radiation generated by the rapid development of electronic products not only affects the normal operation of surrounding equipment, but also has a negative impact on human health. Therefore, there is an urgent need to develop high-performance EMI shielding materials. In recent years, stretchable conductive fibers have attracted great attention because their textiles are becoming an ideal platform for wearable electronic products, such as electronic skin, body health monitors, wearable electromagnetic interference shielding materials, supercapacitors, etc. These textiles can adapt to various deformations, such as twisting, bending and stretching, while maintaining the performance and reliability of the equipment. In addition, conductive fibers can be woven into various patterns with adjustable properties, or combined with other textiles to achieve multifunctionality. Wet spinning is a process that utilizes the double diffusion and phase change process of a high-concentration solution in a coagulation bath, and finally solidifies and forms. It has the characteristics of simple operation, low cost and large-scale preparation of fibers. Fibers prepared by wet spinning have good mechanical properties.
[0004] Many studies are currently devoted to the development of stretchable fibers loaded with various conductive materials. MXene, as a new type of two-dimensional nanomaterial, has excellent conductivity, rich functional groups and good hydrophilicity, and has been widely studied as a wearable electronic device. Although the high conductivity and good hydrophilicity make MXene sheets promising for electromagnetic interference (EMI) shielding and functional textiles, the spinnability of MXene dispersions is poor, and the interfacial interactions between MXene flakes are weak, resulting in poor tensile strength and ductility of its fibers. The easy oxidation of MXene in H2O / O2 environments also severely limits its application.
[0005] In addition, the complex and changing environment and the rapid development of the Internet of Things have brought new challenges to smart electronic fabrics. Due to the fixed components and structural design, it is challenging to achieve adjustable EMI shielding performance of textiles. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a MXene-based fiber, an electromagnetic shielding fabric, and a preparation method and application thereof. The fiber / fabric has good flexibility, mechanical properties, and electromagnetic shielding effectiveness with multimodal response (orientation / humidity / electricity / light). The multimodal response behavior enables the textile to automatically adjust the shielding performance over a wide range when receiving external stimuli.
[0007] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a MXene-based fiber, comprising the following steps:
[0009] The polyvinyl alcohol and MXene solution are mixed uniformly in proportion to obtain a spinning solution, the spinning solution is injected into a calcium ion coagulation bath for solidification, and the solidified fiber is washed and dried to obtain a dry fiber;
[0010] The polymerizable isocyanate (PMDI), acetonitrile and methyl caproate are mixed in proportion to obtain a cross-linking agent;
[0011] The obtained dry fiber is immersed in a cross-linking agent, reacted at 60-80°C for a set time, and then washed and dried to obtain MXene-based fibers.
[0012] As an organic solvent, methyl hexanoate has moderate polarity and can dissolve many organic substances, so it can be used as a medium for isocyanate reactions.
[0013] In some embodiments, in the spinning solution, the mass percentage of polyvinyl alcohol is 10-13 wt %; the mass percentage of MXene is 30-35 mg / mL.
[0014] Preferably, the average size of the MXene sheet is about 3 μm and the thickness is about 1.5 nm.
[0015] In some embodiments, the concentration of calcium ions in the calcium ion coagulation bath is 5-8 wt %.
[0016] In some embodiments, the volume percentage of PMDI in the cross-linking agent is 5%-15%.
[0017] Preferably, in the cross-linking agent, the volume ratio of acetonitrile to methyl hexanoate is 3-5:1.
[0018] Preferably, the obtained dry fiber is immersed in a crosslinking agent, and a crosslinking reaction is carried out at 60-80° C. for 50-100 minutes.
[0019] Further preferably, after the cross-linking reaction is completed, acetone is used to clean the residues on the fiber surface.
[0020] In a second aspect, the present invention provides a MXene-based fiber prepared by the preparation method.
[0021] In a third aspect, the present invention provides the use of the MXene-based fiber in the preparation of electronic skin, health monitors, wearable electromagnetic interference shielding fabrics, wearable thermal therapy fabrics or supercapacitors.
[0022] In a fourth aspect, the present invention provides an electromagnetic shielding fabric woven from the MXene-based fibers.
[0023] The beneficial effects achieved by one or more embodiments of the present invention are as follows:
[0024] (1) In the present invention, the MXene-based fiber is prepared by wet spinning, which has a simple preparation process, does not require complex equipment, is environmentally friendly, has low production cost, and has high yield. The fiber diameter can be controlled by controlling the injection speed of the injection pump and the needle diameter, thereby adjusting the mechanical properties and electromagnetic shielding properties of the MXene-based textile.
[0025] (2) The MXene-based fibers and electromagnetic shielding fabrics prepared by the present invention ensure the reliability and durability of electronic fabrics in extreme environments such as high temperature and high humidity environments by introducing the hydrophobic main chain of PMDI. The fabrics exhibit excellent antioxidant properties in high temperature and high humidity environments, solving the problem of MXene instability in extreme environments.
[0026] (3) The MXene-based fibers prepared by the present invention have good mechanical and electromagnetic shielding properties and can be used to prepare wearable electromagnetic shielding textiles. Such electronic textiles can be used in the fields of health monitors, flexible wearable devices, wearable electromagnetic shielding materials, etc. The textiles can still maintain the performance and reliability of the equipment under various deformations.
[0027] (4) The electromagnetic shielding fabric prepared by using the MXene-based fiber of the present invention can achieve dynamic adjustment of the shielding effect by adjusting the weaving method and changing the rotation angle, which proves its great application potential as an intelligent shielding switch.
[0028] (5) The excellent hygroscopicity of PVA is combined with the efficient light / electrical heat conversion of MXene to realize the wet / light / electrical multimodal response behavior of electromagnetic shielding fabrics, thereby achieving adjustable EMI shielding performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0030] Figure 1 This is the XRD diffraction pattern of the MXene-based fiber prepared in Example 1.
[0031] Figure 2 This is a scanning electron microscope image of the MXene-based fiber prepared in Example 2.
[0032] Figure 3 This is the energy spectrum of the MXene-based fiber prepared in Example 2.
[0033] Figure 4 This is a physical display picture of the electromagnetic shielding fabric prepared in Example 2.
[0034] Figure 5 This is the X-ray photoelectron spectroscopy (XPS) graph of the MXene-based fiber prepared in Example 2.
[0035] Figure 6 This is the stress-strain curve of the MXene-based fiber prepared in Example 2.
[0036] Figure 7 This is a test diagram of the bending stability of the electromagnetic shielding fabric prepared in Example 2.
[0037] Figure 8 This is a graph showing the electromagnetic shielding performance of the electromagnetic shielding fabrics prepared in Example 2 and the comparative example.
[0038] Fig. 9 The graphs are the changes in EMI SE and resistance of the electromagnetic shielding fabrics prepared in Examples 1 and 2 at 95% RH and 65°C.
[0039] Fig.10 This is a diagram of the electromagnetic shielding performance of the MXene-based fiber prepared in Example 2 at different rotation angles.
[0040] Fig.11 This is a diagram of the electromagnetic shielding performance of the MXene-based fiber prepared in Example 2 under light / humidity cycles.
[0041] Fig.12 This is an infrared image of the MXene-based fiber prepared in Example 2 under xenon lamp irradiation. DETAILED DESCRIPTION
[0042] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0043] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0044] Example 1
[0045] A method for preparing MXene-based fibers comprises the following steps:
[0046] (1) Preparation of polyvinyl alcohol (PVA124, viscosity 54-66 mPa·s) solution: 10 g of polyvinyl alcohol (PVA) was dissolved in 90 mL of deionized water, allowed to stand at room temperature for 30 min, and then stirred continuously in an oil bath at 95° C. for 10 h until a clear, transparent, uniform solution was obtained.
[0047] (2) Preparation of MXene aqueous dispersion: Use lithium fluoride / hydrochloric acid (LiF / HCl) mixed solution to etch Ti3AlC2 (MAX phase) precursor, and then layer it to obtain MXene aqueous dispersion. First, add 6.4g of lithium fluoride powder to 80ml of hydrochloric acid (6M) solution and stir at room temperature until dissolved. Then add 4g of MAX to the solution and stir in a 35°C water bath for 24 hours to completely etch the aluminum layer of MAX. Finally, the suspension is centrifuged several times and washed with deionized water until the pH value is ≈6. After shaking the suspension several times and centrifuging, the supernatant obtained is the MXene aqueous dispersion.
[0048] (3) Preparation of spinning solution: Mix the MXene dispersion and the polyvinyl alcohol solution in a ratio of 1:1 (solid content), and stir at room temperature for 1-2 h until the solution is uniform to obtain a PVA / MXene composite spinning solution.
[0049] (4) Preparation of PVA / MXene composite fibers: Pour the above-mentioned PVA / MXene spinning solution into a syringe pump, set the wet spinning parameters, and inject it into a coagulation bath by the syringe pump. The spinning fine flow is formed through a solidification process and a drafting process. At the same time, the fiber is collected in a collection device of the wet spinning equipment, and the obtained fiber is dried at room temperature; the wet spinning conditions are: the injection speed of the syringe is 100 ml / h, and the needle model is selected as 19G (inner diameter 0.72 mm);
[0050] (5) Preparation of PVA / MXene smart electronic fabrics: The obtained fibers were woven on a hand-woven tool to the desired size. Specifically, the fabric was woven using a parallel weaving method. The fabric used to test the shielding performance was 30 mm × 30 mm in size, 400-600 μm in thickness, and 400 g / cm in density. 3 The size of the textile worn on the wooden figure is 60mm×60mm.
[0051] Figure 1 XRD diffraction patterns of MXene-based fibers prepared in different proportions in Example 1, Comparative Example 2 and Comparative Example 4 of the present invention. The XRD peaks prove that the composite fibers are composed of MXene (near 3°) and PVA (near 20°). And as the MXene content increases (Example 1), the MXene peak shifts to the right.
[0052] Example 2
[0053] Compared with Example 1, steps (1) to (4) remain unchanged, and the fiber obtained after drying in step (4) is subjected to chemical crosslinking treatment. The chemically crosslinked fiber is prepared by chemical crosslinking assisted by polymethylene polyphenyl polyisocyanate (PMDI).
[0054] (5) Preparation of a cross-linking agent: Acetonitrile and methyl hexanoate were mixed in a ratio of 4:1 (V / V) to obtain a solution 1; PMDI was dissolved in the solution 1 (1:9, V / V), and stirred to obtain a cross-linking agent.
[0055] (7) The fiber was immersed in the crosslinking agent and reacted in an oven at 70°C for 90 min. The residue on the surface of the sample was then cleaned with acetone. After drying, chemically crosslinked PVA / MXene fibers were finally obtained.
[0056] (8) Preparation of chemically cross-linked PVA / MXene smart electronic fabrics: The obtained fibers were woven on a hand-woven tool. The size of the fabric can be adjusted for shielding performance testing.
[0057] The SEM and EDS results of the MXene-based fibers prepared in Example 2 are as follows: Figure 2 and Figure 3 As shown, it can be seen that the diameter of the MXene-based fiber is about 300 μm, and the MXene nanosheets are evenly distributed inside the fiber.
[0058] The optical image of the electromagnetic shielding fabric prepared in Example 2 is as follows: Figure 4 As shown, it demonstrates its potential as a wearable electronic device.
[0059] The SEM and XPS images of the MXene-based fibers prepared in Example 2 are as follows: Figure 3 and Figure 5 As shown, the results show that the appearance of N element indicates that the chemical cross-linking is successful, confirming the effective interaction between the fiber and PMDI.
[0060] The mechanical properties of the MXene-based fiber prepared in Example 2 were tested, and the stress-strain curve was obtained as shown in Figure 6 Under the synergistic effect of hydrogen bonds, ionic bonds and covalent bonds, chemically cross-linked MXene-based fibers have remarkable mechanical properties. The breaking strength is 220MPa, which proves the excellent mechanical properties of the fiber and meets the requirements of knitting and wearing.
[0061] Figure 7 This is a test diagram of the bending stability of the fabric prepared in Example 2. The sample was attached to a finger, and after 1200 bending cycles, the resistance of the fabric remained stable.
[0062] Comparative Example 1
[0063] The difference from Example 2 is that in step (3), the spinning solution is prepared by mixing the MXene dispersion and the polyvinyl alcohol solution in a ratio of 1:9 (solid content), stirring at room temperature for 2 hours until the solution is uniform, and obtaining a PVA / MXene composite spinning solution, wherein the solid content of MXene is 10%.
[0064] Comparative Example 2
[0065] The difference from Example 2 is that in step (3), the spinning solution is prepared by mixing the MXene dispersion and the polyvinyl alcohol solution in a ratio of 2:8 (solid content), stirring at room temperature for 1-2 hours until the solution is uniform, and obtaining a PVA / MXene composite spinning solution, wherein the solid content of MXene is 20%.
[0066] Comparative Example 3
[0067] The difference from Example 2 is that in step (3), the spinning solution is prepared by mixing the MXene dispersion and the polyvinyl alcohol solution in a ratio of 3:7 (solid content), stirring at room temperature for 2 hours until the solution is uniform, and obtaining a PVA / MXene composite spinning solution, wherein the solid content of MXene is 30%.
[0068] Comparative Example 4
[0069] The difference from Example 2 is that in step (3), the spinning solution is prepared by mixing the MXene dispersion and the polyvinyl alcohol solution in a ratio of 4:6 (solid content), stirring at room temperature for 2 hours until the solution is uniform, and obtaining a PVA / MXene composite spinning solution, wherein the solid content of MXene is 40%.
[0070] The electromagnetic shielding effectiveness of the X-band textiles was measured by Agilent Technologies E8363A electromagnetic wave vector network analyzer for the electromagnetic shielding fabrics prepared in Example 1, Comparative Example 1 and Comparative Example 4. Figure 8 As shown, the results show that the electromagnetic shielding effectiveness of electromagnetic shielding fabric with 50wt.% MXene content can reach 60dB, which has good electromagnetic wave shielding effect.
[0071] Fig. 9 The electromagnetic shielding performance and resistance change diagram of the PVA / MXene smart electronic fabrics prepared in Examples 1 and 2 of the present invention at 95% RH and 65°C. The results show that chemical crosslinking improves the antioxidant properties of the electromagnetic shielding fabric.
[0072] The shielding performance of the electromagnetic shielding fabric prepared in Example 2 at different angles was tested as follows: Fig.10,The results show that by changing the rotation angle of the textile, the shielding performance can be adjusted in the range of 8-58dB, ,proving its potential as a shielding switch.
[0073] The shielding performance of the electromagnetic shielding fabric prepared in Example 2 under the wet / light cycle was tested. Fig.11 The results show that the electromagnetic shielding fabric exhibits an intelligent EMI shielding behavior in an "on / off" state through repeated water absorption and desorption.
[0074] In summary, the multimodal actuation behavior of electromagnetic shielding fabrics is demonstrated.
[0075] The infrared imaging of the electromagnetic shielding fabric prepared in Example 2 adhered to human skin under illumination (xenon lamp simulation) was tested. Fig.12 As shown, the results show that textiles can reach controllable thermal therapy temperature under light and can be used for wearable thermal therapy on the human body.
[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing MXene-based fibers, characterized in that: The steps include: The polyvinyl alcohol and MXene solution are mixed uniformly in proportion to obtain a spinning solution, the spinning solution is injected into a calcium ion coagulation bath for solidification, and the solidified fiber is washed and dried to obtain a dry fiber; The polymerizable isocyanate, acetonitrile and methyl caproate are mixed in proportion to obtain a cross-linking agent; The obtained dry fiber is immersed in a cross-linking agent, reacted at 60-80°C for a set time, and then washed and dried to obtain MXene-based fibers.
2. The method for preparing MXene-based fibers according to claim 1, characterized in that: In the spinning solution, the mass percentage of polyvinyl alcohol is 10-13wt%; the mass percentage of MXene is 30-35mg / mL.
3. The method for preparing MXene-based fibers according to claim 1, characterized in that: In the calcium ion coagulation bath, the concentration of calcium ions is 5-8 wt %.
4. The method for preparing MXene-based fibers according to claim 1, characterized in that: In the cross-linking agent, the volume percentage of PMDI is 5%-15%.
5. The method for preparing MXene-based fibers according to claim 4, characterized in that: In the cross-linking agent, the volume ratio of acetonitrile to methyl hexanoate is 3-5:
1.
6. The method for preparing MXene-based fibers according to claim 5, characterized in that: The obtained dry fiber is immersed in a crosslinking agent, and a crosslinking reaction is carried out at 60-80° C. for 50-100 hours.
7. The method for preparing MXene-based fibers according to claim 6, characterized in that: After the cross-linking reaction is completed, acetone is used to clean the residues on the fiber surface.
8. A MXene-based fiber, characterized in that: Prepared by the preparation method described in any one of claims 1 to 7.
9. Use of the MXene-based fiber according to claim 8 in the preparation of electronic skin, health monitors, wearable electromagnetic interference shielding fabrics, wearable thermal therapy fabrics or supercapacitors.
10. An electromagnetic shielding fabric, characterized in that: It is woven from the MXene-based fibers described in claim 8.
Citation Information
Patent Citations
Physical and chemical double-crosslinking MXene composite film as well as preparation method and application thereof
CN115873279A
Cited By
Providing charge mitigation on a spacesuit via a MXene-based conductive pathway
US12486612B1